Organic-inorganic nano composite pipeline thermal insulation material as well as preparation method and application thereof
Aerogel materials prepared by organic/inorganic nanocomposite dispersants and directional freezing methods have solved the problems of high strength and low thermal conductivity of insulation materials in deep-sea oil and gas transportation, and provided an efficient insulation solution suitable for deep-sea pipelines.
Patent Information
- Application Number
- CN202511461719.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-14
- Publication Date
- 2026-02-06
AI Technical Summary
Existing pipeline insulation materials suffer from a lack of diversity in matrix materials, complex manufacturing processes, and excessively high energy consumption for solvent replacement, making it difficult to meet the requirements of high mechanical strength and low thermal conductivity for deep-sea oil and gas transportation.
Using organic/inorganic nanocomposite dispersants and linear polymers as raw materials, aerogel materials with a three-dimensional network structure are prepared by inducing the nucleation of cement hydration products in the organic/inorganic nanocomposite dispersant solution through directional freezing. Combining the nanocrystal nucleation effect of halloysite nanotubes and the steric hindrance effect of polyoxometalates, a multifunctional thermal insulation material is constructed.
A composite aerogel material with high compressive strength and low thermal conductivity has been developed, which is suitable for deep-sea pipeline insulation. It has a green and environmentally friendly preparation process and a wide range of raw material sources, making it suitable for industrial production.
Smart Images

Figure CN121471703A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of pipeline insulation materials, in particular to an organic-inorganic nanocomposite pipeline insulation material and a preparation method and application thereof. BACKGROUND
[0002] With the further expansion of demand for energy resources, the development of oil and gas has shifted from land to shallow water areas of the seabed, and gradually extended to deep sea (500-1500m) and ultra-deep sea (1500-3000m), and the deep sea area has a high hydrostatic pressure (up to 30.0MPa) and a low external temperature (4℃ / 3000m). Marine pipelines are an important part of the development of offshore oil and gas fields and the main means of oil and gas transportation. However, the temperature of oil and gas will decrease during transportation in marine pipelines, especially for high-density crude oil (such as waxy, gelled, and other high condensation point crude oil), which will gradually precipitate wax components when the oil temperature decreases during pipeline transportation, resulting in increased viscosity of the crude oil and poor flowability, or under the condition of high-pressure long-distance transportation of natural gas, natural gas hydrates are precipitated in the form of loose ice-like solid state, which may cause pipeline blockage and other production accidents. In addition, with the development of exploration operations in deep and ultra-deep water areas in recent years, higher requirements are placed on the high-temperature resistance of the insulation material; the development and utilization of marginal oil fields also require higher total heat transfer coefficient indicators of the insulation pipeline system and higher thermal conductivity of the insulation material.
[0003] Chinese patent CN 108706951A, "A Pipe Insulation Material and Its Preparation Method," discloses a pipe insulation material with alumina aerogel, closed-cell expanded perlite, volcanic ash, and modified palygorskite as its main components. This material exhibits good strength but has a relatively high thermal conductivity. Chinese patent CN 103819644A, "A Pipe Insulation Material with Good Flowability and Its Preparation Method," provides a polyurethane pipe insulation material with good flowability and its preparation method. This material is polyurethane foam, which, while possessing excellent insulation performance, has too low strength and is unsuitable for buried pipeline insulation. Patent CN104419194A, "A Composite Insulation Material of Hollow Glass Microspheres and Polyurethane Resin," discloses an insulation material prepared by combining polyurethane resin and hollow glass microspheres. The resulting material combines the advantages of both, possessing high mechanical strength, oil resistance, and wear resistance. As a thermoplastic material, it is easily processed into complex shapes, making it suitable for special applications. However, this invention does not mention the thermal conductivity and compressive strength of the composite material. Patent CN119081389 A describes a corrosion-resistant thermal insulation material for marine insulation. The process involves acid hydrolysis of plants, followed by filtration and pulping of the filtrate to obtain a cellulose acid hydrolysate and a cellulose acid hydrolysate. The cellulose acid hydrolysate and the cellulose acid hydrolysate are then modified using dopamine hydrochloride and a silane coupling agent, respectively. The modified cellulose, due to the presence of amide groups, exhibits excellent fusion properties in polyurethane systems and can firmly bond to the surface of metal pipelines used for energy transportation in the ocean.
[0004] The oil and gas pipeline materials mentioned in the aforementioned existing patents are mostly polypropylene and polyurethane. Most of these materials improve their physicochemical properties by adding functional materials to the base material. This indicates that the current reliance on a single base material and the lack of applicability of functional materials are among the key challenges addressed in these patents. In the current research and development of oil and gas pipeline materials, the matrix materials mentioned in the patents are still dominated by polypropylene (PP) and polyurethane (PU) systems. Their modification strategies generally employ a composite reinforcement approach by adding functional additives to the base polymer. Existing patent data shows that the homogenization of substrate selection and the multi-dimensional synergistic effects of special additives such as nanofillers and flame retardants have not been fully developed, becoming a major challenge in this field.
[0005] Aerogels, as a novel thermal insulation material, exhibit three core characteristics due to their unique nanoporous network architecture: ultra-lightweight, mesoscopic pore control, and ultra-low thermal conductivity. They have already achieved industrial applications in aerospace thermal protection systems and building energy conservation projects. However, commercial silica-based aerogels face key technological bottlenecks such as weak mechanical properties, complex preparation processes, and high energy consumption for solvent replacement, resulting in high costs for large-scale production. Therefore, focusing on developing novel composite aerogel systems based on new matrix material templates and achieving integrated innovation of multi-scale structural reinforcement and green manufacturing processes through biomimetic mineralization strategies is of paramount importance. Summary of the Invention
[0006] To address the problems of limited matrix materials, complex preparation processes, and high energy consumption in solvent replacement in existing pipeline insulation materials, this application provides an organic-inorganic nanocomposite pipeline insulation material, its preparation method, and its application. Based on the structural characteristics and activity effects of commonly used aerogel materials, cement, and halloysite nanotubes, this application proposes an organic / inorganic nanocomposite pipeline insulation material, its preparation method, and its application, using cement, organic / inorganic nanocomposite dispersants, and linear polymers as raw materials. Aerogels are prepared by inducing the nucleation of cement hydration products in a solution of linear polymers and organic / inorganic nanocomposite dispersants through directional freezing, thereby achieving an organic / inorganic nanocomposite aerogel with a three-dimensional network structure and multiple functions. This aerogel can be used as a composite material for pipeline insulation in various scenarios.
[0007] The specific technical solution of this application is as follows: An organic-inorganic nanocomposite pipe insulation material comprises the following raw materials in the following weight ratios: Linear polymers 2~6, Organic / inorganic nanocomposite dispersant 0.5-1.5, Cement component 3, Hydrophobic component 1, Foaming components 3~9, Organic solvents 20~40.
[0008] The aforementioned organic / inorganic nanocomposite dispersant is obtained by conventional free radical copolymerization of organic monomers and modified halloysite nanotubes, followed by electrostatic interaction with polyoxometalates. The modified halloysite nanotubes mentioned above were obtained by surface modification of pretreated halloysite nanotubes using a silane coupling agent.
[0009] The above-mentioned organic monomers include monomer A, monomer B, and monomer C in a mass ratio of (25~35):(1~3):2; monomer A is any one or a mixture of two or more of acrylic acid, alkali metal salts of acrylic acid, methacrylic acid, and alkali metal salts of methacrylic acid in any proportion; monomer B is isopentenyl polyoxyethylene ether; and monomer C is methacryloylpropyltrimethylammonium chloride or methacryloylpropyltrimethylammonium chloride.
[0010] The mass ratio of the above organic monomers to modified halloysite nanotubes meets the requirement that the polymerization concentration of the free radical copolymerization reaction is 25-30%; the mass ratio of the above polyoxometalate to modified halloysite nanotubes is (1.1~1.4):1.
[0011] The above-mentioned polyoxometalate is phosphomolybdic acid H3[PMo 12 O 40 Or molybdenum silicate H4 [SiMo] 12 O 40 [SiMo] 12 O 40 ] 4- and [PMo 12 O 40 ] 3- Anionic groups can undergo charge assembly with modified halloysite nanotubes.
[0012] The above pretreatment operation involves adding monomer C to halloysite nanotube suspension A to obtain a homogeneous suspension B; the mass fraction of halloysite nanotubes in suspension A is 3-6%; and the mass amount of monomer C is 3% of the mass amount of suspension A.
[0013] The mass amount of the silane coupling agent is 5% of the mass amount of suspension B; preferably, the silane coupling agent is γ-methacryloyloxypropyltrimethoxysilane.
[0014] The organic / inorganic nanocomposite dispersant of this application is obtained by a conventional free radical copolymerization reaction of monomer A (acrylic acid, alkali metal salt of acrylic acid, methacrylic acid, alkali metal salt of methacrylic acid, or a mixture of two or more of these monomers in any proportion), monomer B (isoprene alcohol polyoxyethylene ether), monomer C (methacryloylpropyltrimethylammonium chloride or acryloylpropyltrimethylammonium chloride), and modified halloysite nanotubes (M-HNTs), followed by electrostatic interaction with polyoxometalates (POMs). The preparation of the organic / inorganic nanocomposite dispersant includes the following steps: (a) Halloysite nanotube modification reaction: Halloysite nanotube powder is added to deionized water to prepare a mass fraction of 3-6%. (a) Suspension A: Adjust the temperature of suspension A to 60°C, add monomer C to obtain suspension B, then add silane coupling agent, and continue stirring to obtain modified halloysite nanotubes; (b) Copolymerization reaction: When the temperature of the modified halloysite nanotubes obtained in step (a) drops to 35-55°C and remains constant, add monomer A, monomer B and monomer C, as well as oxidant and reducing agent, and carry out free radical copolymerization reaction at 35-55°C, wherein the polymerization concentration of the free radical copolymerization reaction is 25-30%; (c) Electrostatic assembly reaction: Add polyoxometalate to the system in step (b), carry out conventional stirring reaction, and obtain organic / inorganic nanocomposite dispersant.
[0015] Preferably, the oxidant is any one of water-soluble ammonium persulfate, sodium persulfate, or potassium persulfate, and the amount of oxidant used is 0.12 to 0.6% of the total mass of the organic monomers.
[0016] Preferably, the reducing agent is one or two of sodium metabisulfite, sodium sulfite, sodium bisulfite, sodium dithionite, sodium thiosulfate, and ferrous sulfate, combined in any proportion, and the mass ratio of the reducing agent to the oxidizing agent is 1:2.
[0017] Specifically, the preparation method of organic / inorganic nanocomposite dispersants includes the following steps: (a) Halloysite nanotube (HNT) modification reaction: First, halloysite nanotubes (HNTs) powder was slowly added to deionized water and stirred at 20°C to obtain a suspension A with a mass fraction of 3-6%. The temperature of suspension A was adjusted to 60°C, and monomer C was added to obtain suspension B. The reaction temperature was kept constant, and the mixture was stirred again. Then, γ-methacryloyloxypropyltrimethoxysilane was added, and stirring continued. The stirring rate and stirring time remained constant in each stage of the reaction. The stirring speed was 600-1000 r / min, and the stirring time was 2-5 h to obtain the modified halloysite nanotubes. The mass of monomer C added was 3% of that in suspension A, and the mass of γ-methacryloyloxypropyltrimethoxysilane added was 5% of that in suspension B. (b) Copolymerization: After the system temperature of the modified halloysite nanotubes (M-HNTs) obtained in step (a) is lowered to 35-55℃ and kept constant, monomers A, B and C, as well as oxidant and reducing agent are mixed and added, and reacted at 35-55℃ for 3-6 hours to carry out free radical copolymerization reaction. The free radical copolymerization reaction is an aqueous free radical copolymerization reaction, and the polymerization concentration of the free radical copolymerization reaction is 25-30%.
[0018] (c) Electrostatic assembly reaction: Polyoxometalates (POMs) were added to the system in step (b), with the mass ratio of POMs to modified halloysite nanotubes being 1.1 to 1.4:1. The reaction was carried out under conventional stirring at a temperature of 40 to 50 °C for 3 to 6 h and a stirring rate of 800 to 1200 r / min to obtain an organic / inorganic nanocomposite dispersant.
[0019] The addition of monomer C during the halloysite nanotube (HNTs) modification process is to improve the dispersibility of halloysite nanotubes through charge adsorption, thereby significantly enhancing the release of HNTs activity. Through coupling agent modification, HNTs are grafted onto the molecular chain of the composite dispersant via Si-O chemical bonds, fully leveraging the activity of HNTs.
[0020] Halloysite carries a negative charge on its outer surface, while monomer C carries a positive charge. According to the principle of electrostatic attraction, "opposites attract," they strongly attract each other. This attraction forms the basis of halloysite modification: by utilizing this electrostatic attraction, monomer C can act as a modifier, encapsulating the outer surface of halloysite nanotubes through intercalation or adsorption, successfully converting its surface charge from negative to positive. This modified halloysite exhibits superior performance in terms of dispersibility, compatibility with polymer matrices, and its role as a drug carrier.
[0021] The linear polymer is at least one of polyethylene glycol, polyacrylamide, polyvinyl alcohol, and polyethyleneimine, and the concentration of the linear polymer solution is 5 wt%; the concentration of the organic / inorganic nanocomposite dispersant is 3 wt%. The cement mentioned above is any one of sulfoaluminate cement, high aluminate cement, phosphate cement, etc.; the hydrophobic component mentioned above is any one of methyltrimethoxysilane or triethoxyfluorosilane, with a concentration of 10 wt%; the foaming component mentioned above is any one of hydrogen peroxide, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate, with a concentration of 30 wt%; the organic solvent mentioned above is any one of methanol, ethanol, isopropanol.
[0022] This application uses cement-based materials as a new matrix material; it utilizes linear polymers and composite dispersants as "organic templates" and, with the assistance of a physical field provided by directional freezing, mimics the biomineralization process to actively guide cement hydration products to nucleate, grow, and assemble into a strong and tough three-dimensional network skeleton with a multi-level ordered structure in a nanoscale and controllable manner.
[0023] A method for preparing an organic / inorganic nanocomposite pipe insulation material includes the following steps: (1) adding an organic / inorganic nanocomposite dispersant to a linear polymer solution, then slowly adding cement components and organic solvents, and stirring until uniform; (2) adding a hydrophobic component to the solution in step (1) and stirring to react; (3) adding a foaming component to the solution in step (2) and stirring to react; (4) pouring the thoroughly mixed slurry from step (3) into a freezing mold and using liquid nitrogen for directional freezing; (5) after freezing, thawing the entire freezing mold at room temperature and waiting for it to return to room temperature; (6) after returning to room temperature, placing the entire mold in an oven for drying, thereby obtaining the organic / inorganic nanocomposite pipe insulation material.
[0024] The stirring time for step (1) is 1~3 h and the stirring rate is 1000~2500 r / min; the stirring time for step (2) is 0.5~1 h and the stirring rate is 1000~1500 r / min; the stirring time for step (3) is 1~5 min and the stirring rate is 500~1000 r / min; the freezing time for step (4) is 2~4 h and the freezing temperature is -180~-150℃; the drying temperature for step (6) is 60-80℃ and the drying time is 12~24 h.
[0025] The organic / inorganic nanocomposite pipe insulation material claimed in this patent uses organic / inorganic nanocomposite dispersants, linear polymers, and cement as main raw materials. Cement acts as the skeleton, providing high mechanical strength. The organic / inorganic nanocomposite dispersant, on the one hand, possesses carboxyl groups and a multidimensional spatial network structure that effectively disperses cement components; on the other hand, halloysite nanotubes in the dispersant can fully utilize their nanocrystal nucleation and size effects in cement-based materials, further improving the mechanical properties of the insulation material. Furthermore, the newly added polyoxometalate POM units, due to their steric hindrance effect, further support the skeletal function of cement. Regarding the aerogel preparation process, qualitative freezing pore-forming can significantly improve the strength of the aerogel and further reduce its thermal conductivity. Based on the high mechanical strength, durability, and excellent high-temperature stability of traditional cement materials, this application introduces it as a matrix into an organic-inorganic nanohybrid aerogel insulation system. Through ice template directional freezing technology, the orientation growth of ice crystals is precisely controlled, achieving three-dimensional directional construction of the composite aerogel pore structure, thereby breaking through the bottleneck of synergistic optimization of mechanical properties and insulation performance in traditional thermal insulation materials.
[0026] This organic / inorganic nanocomposite pipe insulation material is suitable for pipes in any field, especially for deep-sea applications.
[0027] This application has the following advantages over the prior art: This application incorporates halloysite nanotubes, a naturally occurring nanoscale material with a unique tubular structure, into the preparation of composite aerogels. On one hand, by synergistically utilizing the heterogeneous nucleation effect and nanoscale confinement effect of nanocrystal nuclei, it induces the formation of a highly oriented crystal network and a dense interface in the multi-level structural design of the material. This optimizes and controls the internal stress distribution of the insulation material, significantly improving its compressive strength and toughness. On the other hand, due to their inner diameter of 10-150 nm, they can embed other active materials within the multilayer aluminosilicate shell and its pores, providing an important technical path for developing a new generation of insulation systems that combine lightweight and high reliability. Therefore, by adding cement and halloysite nanotubes to traditional aerogel components, both the supramolecular interactions between polymer chains and the structural network reinforcement are utilized, ultimately achieving an organic / inorganic nanocomposite aerogel insulation material with high compressive strength, high hydrophobicity, and excellent thermal insulation performance. (2) The method for preparing an organic / inorganic nanocomposite pipe insulation material provided in this application uses raw materials that are widely available and in line with the concept of green chemistry. The preparation method is simple, highly operable, and suitable for industrial production. By regulating the self-assembly behavior of nanoparticles and the dynamic balance of the phase change interface, the synergistic optimization of the compressive strength and thermal conductivity of the material is successfully achieved, which has significant feasibility for large-scale preparation. (3) This application improves the various performance characteristics of thermal insulation materials by controlling the addition ratio of cement, foaming components, linear polymers and organic / inorganic nanocomposite dispersants, as well as hydrophobic components and organic solvents, and the temperature, rate and time of the directional freezing process. (4) The technical means of this application innovatively integrate the advantages of inorganic building materials and aerogel technology, and combine them with green and environmentally friendly process paths, providing a theoretical basis and technical paradigm for the development of new functional materials with both structural strength and high-efficiency heat insulation for engineering pipeline insulation systems; the preparation process of the materials used in this application is simple and easy to implement, and the raw materials selected have green and environmentally friendly characteristics and are in line with the concept of sustainable development, which has developed an innovative solution for the field of pipeline insulation and heat insulation, and provided technical reference for the research and development of new environmentally friendly heat insulation materials. Attached Figure Description
[0028] Figure 1 This is the preparation process of the organic / inorganic nanocomposite pipe insulation material of this application; Figure 2 The image shows the microstructure of the organic / inorganic nanocomposite thermal insulation material obtained in Example 5. Detailed Implementation
[0029] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0030] Unless otherwise specified, all chemical reagents and materials in this invention are purchased from the market or synthesized from raw materials purchased from the market.
[0031] The preparation steps of the organic / inorganic nanocomposite dispersants used in the various embodiments and comparative examples of this application are as follows: (a) Halloysite nanotube (HNT) modification reaction: First, halloysite nanotubes (HNTs) powder was slowly added to deionized water and stirred at 20°C to obtain a suspension A with a mass fraction of 3-6%. The temperature of suspension A was adjusted to 60°C, and monomer C was added to obtain suspension B. The reaction temperature was kept constant, and the mixture was stirred again. Then, γ-methacryloyloxypropyltrimethoxysilane was added, and stirring continued. The stirring rate and stirring time remained constant in each stage of the reaction. The stirring speed was 600-1000 r / min, and the stirring time was 2-5 h to obtain the modified halloysite nanotubes. The mass of monomer C added was 3% of that in suspension A, and the mass of γ-methacryloyloxypropyltrimethoxysilane added was 5% of that in suspension B. (b) Copolymerization: After the system temperature of the modified halloysite nanotubes (M-HNTs) obtained in step (a) is lowered to 35-55℃ and kept constant, monomers A, B and C, as well as oxidant and reducing agent are mixed and added, and reacted at 35-55℃ for 3-6 hours to carry out free radical copolymerization reaction. The free radical copolymerization reaction is an aqueous free radical copolymerization reaction, and the polymerization concentration of the free radical copolymerization reaction is 25-30%.
[0032] (c) Electrostatic assembly reaction: Polyoxometalates (POMs) were added to the system in step (b), with the mass ratio of POMs to modified halloysite nanotubes being 1.1 to 1.4:1. The reaction was carried out under conventional stirring at a temperature of 40 to 50 °C for 3 to 6 h and a stirring rate of 800 to 1200 r / min to obtain an organic / inorganic nanocomposite dispersant.
[0033] The raw material composition of the organic / inorganic nanocomposite dispersant in each embodiment is shown in Table 1 below, where the feed ratio is the mass ratio of monomer A, monomer B and monomer C.
[0034] Table 1. Raw material ratios of organic / inorganic nanocomposite dispersants in each embodiment and comparative example.
[0035] The process parameters of the organic / inorganic nanocomposite dispersants in each embodiment are shown in Table 2 below, where the amounts of oxidant and reducing agent are percentages of the total mass of the organic monomers.
[0036] Table 2. Process parameters of organic / inorganic nanocomposite dispersants in each embodiment.
[0037] The raw material ratios of the various components in the organic / inorganic nanocomposite pipe insulation materials in each embodiment and comparative example are shown in Table 3 below: Table 3 Raw material ratio table for Examples 1-8 and Comparative Examples 1-4
[0038] The preparation method of organic / inorganic nanocomposite pipe insulation material in each embodiment and comparative example includes the following steps: (1) At room temperature, add organic / inorganic nanocomposite dispersant to the dissolved linear polymer solution, and then slowly add cement component and organic solvent, and stir evenly; (2) Add hydrophobic component to the solution in step (1) and stir to react; (3) Add foaming component to the solution in step (2) and stir to react; (4) Pour the slurry of step (3) that is fully mixed evenly into a freezing mold and use liquid nitrogen for directional freezing; (5) After freezing, thaw the entire freezing mold at room temperature and wait for it to return to room temperature; (6) After returning to room temperature, put the entire mold into an oven for drying, and obtain organic / inorganic nanocomposite pipe insulation material.
[0039] In Table 3, when applied to the preparation process of organic / inorganic nanocomposite pipe materials, the concentration of the linear polymer solution is 5 wt%, the concentration of the organic / inorganic nanocomposite dispersant is 3 wt%, the concentration of the hydrophobic component is 10 wt%, and the concentration of the foaming component is 30 wt%.
[0040] The process parameters for the examples and comparative examples (time: stirring time / h; rate: stirring rate / r / min) are shown in Table 4 below: Table 4. Time Conditions for Examples 1-8 and Comparative Examples 1-4
[0041] Test Example: Performance Testing Organic / inorganic nanocomposite pipe insulation materials were prepared according to the proportions and processes outlined in Tables 1-4, resulting in Examples 1-9 and Comparative Examples 1-4. The materials from the examples and comparative examples were subjected to performance testing. The compressive strength and thermal conductivity tests were conducted according to GB / T 34336-2017, "Nanoporous Aerogel Composite Insulation Products". The test results are shown in Table 5 below. Table 5 Performance test data of Examples 1-8 and Comparative Examples 1-4
[0042] As can be seen from the experimental results in Table 5, the organic / inorganic nanocomposite aerogel pipe insulation material developed through a series of examples (1-9) exhibits triple composite advantages: excellent mechanical strength, ultra-lightweight properties, and superior thermal insulation performance. This material system, through organic-inorganic hybrid technology, successfully achieves synergistic optimization of low-cost preparation processes and high-performance insulation indicators, providing an innovative solution for the field of energy-saving materials for industrial pipelines.
[0043] In addition, we found that the compressive strength effects of Examples 1 to 9 are also different. The ratio between the linear polymer, the organic / inorganic nanocomposite dispersant, and the foaming component can affect its workability. This is because, on the one hand, the organic / inorganic nanocomposite dispersant effectively disperses cement, and on the other hand, there is a supramolecular interaction between the linear polymer and the organic / inorganic nanocomposite dispersant, which together achieves a synergistic enhancement of the aerogel skeleton strength. Therefore, the ratio of the two should not be too high or too low. Preferably, the mass ratio of linear polymer to organic / inorganic nanocomposite dispersant is 4:1. If the content of halloysite nanotubes is too high, the tubular structure will cause entanglement of the carboxylic acid groups on the same molecular chain, forming a cage effect, which will result in low dispersibility of cement components and make it difficult to improve the strength of the material. If the content of linear polymer is too low, the material skeleton will be difficult to form, and there is no way to improve the strength of the material.
[0044] Compared with Examples 1-9, Comparative Examples 1, 2 and 3 showed significantly worse performance, further confirming that the absence of the corresponding organic / inorganic nanocomposite dispersant components and cement components or the use of conventional halloysite nanotubes could not improve the performance of the materials.
[0045] The data from Example 5 and Comparative Example 4 show that the steric hindrance effect of missing POM reduces the supramolecular interaction between the linear polymer and the organic / inorganic nanocomposite dispersant, especially in terms of the strength of the aerogel skeleton.
[0046] Therefore, by controlling the multi-scale interfacial structure of linear polymer / cement matrix using directional freezing technology, and synergizing the multifunctional coupling effects of organic / inorganic nanocomposite dispersants, hydrophobic modifiers, and foaming agents, a thermal insulation material suitable for deep-sea pipelines was successfully prepared. This material system achieves a triple synergy of performance: a three-dimensional interpenetrating network skeleton (high compressive strength), a hydrophobic surface (high hydrophobicity), and a high-porosity thermal insulation structure (low thermal conductivity), providing an innovative solution for pipeline insulation under deep-sea pipeline conditions.
[0047] The technical solution of this application has been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this invention. The descriptions of the embodiments above are only for the purpose of helping to understand the method and core ideas of this invention, including the best mode, and also to enable any person skilled in the art to practice this invention. It should be noted that for those skilled in the art, several improvements and modifications can be made to this invention without departing from the principles of this invention, and these improvements and modifications also fall within the protection scope of the claims of this invention. The scope of protection of this patent is defined by the claims and may include other embodiments that can be conceived by those skilled in the art. If these other embodiments have structural elements that are not different from the wording of the claims, or if they include equivalent structural elements that are not substantially different from the wording of the claims, then these other embodiments should also be included within the scope of the claims. For those skilled in the art, it is understood that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of this invention, and the scope of this invention is defined by the appended claims and their equivalents.
Claims
1. An organic-inorganic nanocomposite pipe insulation material, characterized in that, Raw materials including the following parts by weight: Linear polymers 2~6, Organic / inorganic nanocomposite dispersant 0.5-1.5, Cement component 3, Hydrophobic component 1, Foaming components 3~9, Organic solvent 20~40; The organic / inorganic nanocomposite dispersant is obtained by conventional free radical copolymerization of organic monomers and modified halloysite nanotubes, and then electrostatically interacted with polyoxometalates. The modified halloysite nanotubes were obtained by surface modification of pretreated halloysite nanotubes using a silane coupling agent.
2. The organic-inorganic nanocomposite pipe insulation material according to claim 1, characterized in that: The organic monomers include monomer A, monomer B, and monomer C in a mass ratio of (25~35):(1~3):2; monomer A is any one or a mixture of two or more of acrylic acid, alkali metal salts of acrylic acid, methacrylic acid, and alkali metal salts of methacrylic acid in any proportion; monomer B is isopentenyl polyoxyethylene ether; and monomer C is methacryloylpropyltrimethylammonium chloride or acryloylpropyltrimethylammonium chloride.
3. The organic-inorganic nanocomposite pipe insulation material according to claim 1, characterized in that: The mass ratio of the organic monomer to the modified halloysite nanotubes meets the requirement that the polymerization concentration for the free radical copolymerization reaction is 25-30%; the mass ratio of the polyoxometalate to the modified halloysite nanotubes is (1.1~1.4):1; preferably, the polyoxometalate is phosphomolybdic acid H3[PMo 12 O 40 Or molybdenum silicate H4 [SiMo] 12 O 40 ].
4. The organic-inorganic nanocomposite pipe insulation material according to claim 1, characterized in that: The pretreatment operation involves adding monomer C to halloysite nanotube suspension A to obtain a homogeneous suspension B; the mass fraction of halloysite nanotubes in suspension A is 3-6%; and the mass amount of monomer C is 3% of the mass amount of suspension A.
5. The organic-inorganic nanocomposite pipe insulation material according to claim 4, characterized in that: The mass amount of the silane coupling agent is 5% of the mass amount of suspension B.
6. The organic-inorganic nanocomposite pipe insulation material according to claim 1, characterized in that, The preparation of the organic / inorganic nanocomposite dispersant includes the following steps: (a) Halloysite nanotube modification reaction: Halloysite nanotube powder is added to deionized water to prepare a suspension A with a mass fraction of 3-6%. The temperature of suspension A is adjusted to 60°C, monomer C is added to obtain suspension B, and then a silane coupling agent is added. After stirring and reacting, the modified halloysite nanotubes are obtained; (b) Copolymerization reaction: When the temperature of the modified halloysite nanotube system obtained in step (a) drops to 35-55°C and remains constant, monomer A, monomer B and monomer C, as well as oxidant and reducing agent are mixed and added, and a free radical copolymerization reaction is carried out at a temperature of 35-55°C, wherein the polymerization concentration of the free radical copolymerization reaction is 25-30%; (c) Electrostatic assembly reaction: Polyoxometalate is added to the system in step (b), and a conventional stirring reaction is carried out to obtain the organic / inorganic nanocomposite dispersant.
7. The organic-inorganic nanocomposite pipe insulation material according to claim 6, characterized in that: The oxidant is any one of water-soluble ammonium persulfate, sodium persulfate, or potassium persulfate, and the amount of oxidant used is 0.12~0.6% of the total mass of the organic monomers; the reducing agent is one or two of sodium metabisulfite, sodium sulfite, sodium bisulfite, sodium dithionite, sodium thiosulfate, and ferrous sulfate, combined in any proportion, and the mass ratio of the reducing agent to the oxidant is 1:
2.
8. The organic-inorganic nanocomposite pipe insulation material according to claim 1, characterized in that: The linear polymer is at least one of polyethylene glycol, polyacrylamide, polyvinyl alcohol, and polyethyleneimine, and the concentration of the linear polymer solution is 5 wt%. The concentration of the organic / inorganic nanocomposite dispersant is 3 wt%. The cement is any one of sulfoaluminate cement, high aluminate cement, and phosphate cement. The hydrophobic component is any one of methyltrimethoxysilane or triethoxyfluorosilane, and the concentration is 10 wt%. The foaming component is any one of hydrogen peroxide, sodium bicarbonate, ammonium carbonate, and ammonium bicarbonate, and the concentration is 30 wt%. The organic solvent is any one of methanol, ethanol, and isopropanol.
9. A method for preparing an organic-inorganic nanocomposite pipe insulation material according to any one of claims 1-7, characterized in that, The process includes the following steps: (1) adding organic / inorganic nanocomposite dispersant to a linear polymer solution, then slowly adding cement components and organic solvents, and stirring until uniform; (2) adding hydrophobic components to the solution in step (1) and stirring to react; (3) adding foaming components to the solution in step (2) and stirring to react; (4) pouring the well-mixed slurry from step (3) into a freezing mold and using liquid nitrogen for directional freezing; (5) after freezing, thawing the entire freezing mold at room temperature and waiting for it to return to room temperature; (6) after returning to room temperature, placing the entire mold in an oven for drying, thus obtaining organic / inorganic nanocomposite pipe insulation material.
10. The preparation method according to claim 8, characterized in that: The stirring time in step (1) is 1~3 h, and the stirring rate is 1000~2500 r / min; the stirring time in step (2) is 0.5~1 h, and the stirring rate is 1000~1500 r / min; the stirring time in step (3) is 1~5 min, and the stirring rate is 500~1000 r / min; the freezing time in step (4) is 2~4 h, and the freezing temperature is -180~-150℃; the drying temperature in step (6) is 60-80℃, and the drying time is 12~24 h.
11. The application of the organic-inorganic nanocomposite pipe insulation material according to any one of claims 1-7 in the deep-sea field.
Citation Information
Patent Citations
Pipe insulating material with good fluidity and preparation method thereof
CN103819644A
Hollow glass micro-bead and polyurethane resin composite thermal insulation material
CN104419194A
Pipeline thermal insulation material and preparation method thereof
CN108706951A
Corrosion-resistant thermal insulation material for ocean thermal insulation
CN119081389A